2007
DOI: 10.1116/1.2717195
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial overgrowth of GaN nanocolumns

Abstract: Reactive molecular-beam epitaxy of GaN layers directly on 6H-SiC(0001) Appl. Phys. Lett. 75, 944 (1999); 10.1063/1.124562Low temperature sapphire nitridation: A clue to optimize GaN layers grown by molecular beam epitaxy GaN nanocolumns of exceptional crystalline quality have been grown by molecular beam epitaxy on both silicon ͑111͒ and sapphire ͑0001͒ substrates. Reflection high energy electron diffraction produces a unique diffraction pattern for in situ verification of columnar growth. Subsequent molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Comparable results have been observed for nanocolumnar GaN films grown in a low surface mobility regime [36]. This again justifies the application of the Scherrer formula to calculate ξ ⊥ .…”
Section: Fig 4 Sem Micrographs Of Fracture Cross-section (A) and Tosupporting
confidence: 61%
“…Comparable results have been observed for nanocolumnar GaN films grown in a low surface mobility regime [36]. This again justifies the application of the Scherrer formula to calculate ξ ⊥ .…”
Section: Fig 4 Sem Micrographs Of Fracture Cross-section (A) and Tosupporting
confidence: 61%
“…Below this temperature the film no longer contains isolated nanowires, and by 760 1C it resembles a pitted, continuous film. There is variation from group to group on the center of the range of substrate temperatures for GaN nanowire growth with MBE [7][8][9][10][11], such that the total range of reported temperatures extends from 720 to 900 1C, but no one group has reported successful growth over a temperature range broader than 40 1C. The variation from system to system is most likely due to shifts in the growth window with variations in plasma source products, Ga flux, and temperature calibration, none of which are easily measured to high accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…Specific examples of the variety of noncatalytic nucleation conditions include seeded growth [9], growth on Si (111) [10][11][12][13][14][15][16][17][18][19][20][21][22], growth on sapphire or Si (111) [1][2][3][4][5][6][7][8], growth on Si (1 0 0) [23], growth with intentional surface nitridation [10], growth with AlN buffer layers [5,24,25] and growth without AlN buffer layers [26,27]. In Fig.…”
Section: Article In Pressmentioning
confidence: 99%
“…We reported the epitaxial overgrowth of continuous GaN film on GaN nanocolumns in 2002 [15], but Be was not used and the formation of dislocations was not discussed in that paper. More recently, Averett et al also reported the overgrowth of GaN nanocolumns, but the surface morphology was not smooth; many pits and facets remained at the coalescence boundary [16].…”
Section: Contributedmentioning
confidence: 98%